PERILAKU PETUGAS PENGUMPUL SAMPAH UNTUK MELINDUNGI DIRINYA DARI PENYAKIT BAWAAN SAMPAH DI WILAYAH PATANGPULUHAN YOGYAKARTA TAHUN 2009 - Adnani, Hariza (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2010)
Background : Human activities in using of nature always leaving the rest that are consideredare not useful anymore, so treated as waste products, namely garbage and waste. If the wasteis not managed properly, it will negatively impact health. Therefore there is need for theprevention of negative influences to avoid or use personal protective. The purpose of thisresearch is to know knowledge about the types of garbage collectors , the knowledge workers ofthe garbage collector garbage congenital diseases, and the behavior of garbage collectionworkers in protecting themselves against inherited diseases.Methods: This kind of research is the research evaluation, which includes the formativeevaluation (emphasis on process rather than product). While the research approach used isqualitative. Research subjects in this study are to garbage collectors officers Dumpster (TPS)which use pushcart. Data collection techniques will be used is the observation by participating(participation observation), and in-depth interviews (in-depth Interviewing). Techniques of dataanalysis performed using data reduction, data display the data verification.Conclusion : The conclusions to be drawn from this study are: First, knowledge about the typesof garbage collectors personal protection device which must be worn during most of the work isstill lacking. Second, the knowledge workers of the garbage collector garbage congenitaldiseases mostly still less understood. Third, the behavior of garbage collection workers inprotecting themselves against inherited diseases is less trash to the efforts carried out beforetouching the garbage, and is good for the efforts undertaken after touching garbage. All of themare supported by the lack or ignorance of understanding about self health (Hygiene Sanitation).Keywords: Behavior, personal protection device, congenital disease trash